O ALUNO COM SÍNDROME DE SMITH-LEMLI-OPITZ NO ATENDIMENTO EDUCACIONAL ESPECIALIZADO: UM ESTUDO DESCRITIVO - Dias, Israel Rocha (2020)
This study entitled student with Smith-Lemli-Opitz syndrome in specialized educational care: a descriptive , presents data surveys produced in a research in the Doctorate in Education course of the Graduate Program at Universidade Federal do Espírito San